Electrostatic Sampling of Patient Breath for Pathogen Detection: A Pilot Study - Ladhani, Laila; Pardon, Gaspard; Moons, Pieter; Goossens, Herman; van der Wijngaart, Wouter (Frontiers in Mechanical Engineering, 2020)
Collecting samples for diagnosis of respiratory infections can be invasive and highly uncomfortable for patients; with sampling techniques ranging from nasal or throat swabs to bronchoalveolar lavage. In this work, we explore the electrostatic capture of exhaled pathogens as a non-invasive sampling method for rapid diagnosis in a primary care setting. A pilot study at primary care centers in Belgium enrolled 20 patients presenting with flu-like symptoms whose diagnosis was determined by nasopharyngeal (NP) swabs. We collected exhaled aerosol particles from infected patients using a breath electrostatic sampler (BESS) and using filters, following an extremely light procedure consisting of five normal exhales. All samples were analyzed using a commercial multiplex q-RT-PCR panel assay. Staphylococcus aureus (S. aureus) was detected from BESS samples of 7 patients; 3 of whom were in agreement with their corresponding diagnoses. The BESS method was negative for exhaled viruses. We detected viruses, but no bacteria, with the filters, but the results showed no correlation with the corresponding diagnosis. Our results indicate that electrostatic sampling of exhaled breath is a technique and approach potentially suited for the primary care setting, where it might constitute a helpful diagnostic device.